Analysis of Two Polyhydroxyalkanoate Synthases in Bradyrhizobium japonicum USDA 110 - Quelas, Juan Ignacio (2013)
Bradyrhizobium japonicum USDA 110 has five polyhydroxyalkanoate (PHA) synthases (PhaC) annotated in its genome: bll4360 (phaC1), bll6073 (phaC2), blr3732 (phaC3), blr2885 (phaC4), and bll4548 (phaC5). All these proteins possess the catalytic triad and conserved amino acid residues of polyester synthases and are distributed into four different PhaC classes. We obtained mutants in each of these paralogs and analyzed phaC gene expression and PHA production in liquid cultures. Despite the genetic redundancy, only phaC1 and phaC2 were expressed at significant rates, while PHA accumulation in stationary-phase cultures was impaired only in the phaC1 mutant. Meanwhile, the phaC2 mutant produced more PHA than the wild type under this condition, and surprisingly, the phaC3 transcript increased in the phaC2 background. A double mutant, the phaC2 phaC3 mutant, consistently accumulated less PHA than the phaC2 mutant. PHA accumulation in nodule bacteroids followed a pattern similar to that seen in liquid cultures, being prevented in the phaC1 mutant and increased in the phaC2 mutant in relation to the level in the wild type. Therefore, we used these mutants, together with a phaC1 phaC2 double mutant, to study the B. japonicum PHA requirements for survival, competition for nodulation, and plant growth promotion. All mutants, as well as the wild type, survived for 60 days in a carbon-free medium, regardless of their initial PHA contents. When competing for nodulation against the wild type in a 1:1 proportion, the phaC1 and phaC1 phaC2 mutants occupied only 13 to 15% of the nodules, while the phaC2 mutant occupied 81%, suggesting that the PHA polymer is required for successful competitiveness. However, the bacteroid content of PHA did not affect the shoot dry weight accumulation.